Growth Strategy Analysis Of Merger Pt. Bank Cimb Niaga Tbk With Lippo Bank - Hardiyanto, Purnawan; Marlitta Stefia, Cheryl (Riviera Publishing, 2022)
Introduction: PT. Bank CIMB Niaga Tbk. is a bank which was founded on September 26, 1955 and is the 5th largest bank in Indonesia based on asset value. The initial purpose of establishing this bank is to build values and professionalism, especially in the banking sector. Method: To achieve this goal, research was carried out with using pure quantitative research and then to process the data used descriptive quantitative research. Secondary data sources in this study from the internet or research from another author. Results: The main reason for the merger between the two banks is due to the rules applied by Bank Indonesia regarding the single presence policy. Rule It states that a party is only allowed to be the owner of shares controllers on one bank only. When any party is affected by the rule, then given three options for restructuring, including: merger or acquisition, transfer shares and the formation of a holding company. Changes due to the merger can have an effect on changes in performance. Performance need evaluated regularly because it is very important to maintain company productivity. Conclusion: From the calculation data above, it can be concluded that the merger process is not always bring positive results. This can be seen from the significant decrease in net profit margin and net income total assets. Many things caused the decline in both parts. One of them occurs due to an increase in operating costs which was delegated to Bank CIMB Niaga after the merger. This condition is due to the addition of the number of ATM machines and the development of technological systems that applied to some access and service features.